Characteristics of phosgene aspiration lung injury analyzed based on transcriptomics and proteomics - Wang, Li-Na; Shao, Yi-Ru; Wang, Peng-Fei; Lv, Jiang; He, Dai-Kun (Frontiers in Genetics, 2024)
Background: Phosgene is a chemical material widely used worldwide. No effective method has been developed to reverse its pathological injuries. Some studies have shown that neuronal inflammation in lung tissue is involved, but the specific mechanism has not been reported.To analyze the expression alterations of whole transcriptome gene sequencing bioinformatics and protein expression profile in lung tissue after phosgene aspiration lung injury (P-ALI) and find the main factors and pathways affecting the prognosis of P-ALI.Methods: Rat models of P-ALI were made by phosgene. Rats were divided into a P-ALI group and a blank group. Hematoxylin-eosin (HE) staining and lung wet/dry ratio measurement were used to evaluate the lung injury. The levels of inflammatory factors were measured by ELISA. Highthroughput sequencing was used to measure the expression profile of each gene. Protein expression profiles were determined by label-free relative quantification of the differential proteome.Results: Lung injury such as the disordered structure of alveolar wall and inflammatory factors (IL-1β, IL-18, and IL-33) were significantly increased in the P-ALI group (P< 0.05). There were 225 differentially expressed lncRNAs, including 85 up-regulated and 140 down-regulated genes. They were also the genomes with the most significant changes in transcriptome gene expression, mainly constituting cytoplasmic, synaptic structures and transporters, and involved in amino acid and carbon metabolism. There were 42 differentially expressed circRNAs, including 25 up-regulated genes and 17 down-regulated genes, mainly involved in cell composition, growth, differentiation, and division. There were only 10 differentially expressed miRNAs genes, all up-regulated and mainly involved in the inflammatory response pathway. Proteome identification showed 79 differentially expressed proteins. KEGG enrichment analysis showed that it was mainly involved in the N-glycan biosynthesis pathway.We discovered that differentially regulated genes (lncRNAs, circRNAs, and miRNAs) were primarily associated with neuronal reflexes and synaptic signaling, including neurotransmitter transmission, ion signaling pathway conduction, neuronal projection, and synaptic vesicle circulation. They affected inflammatory factors and other metabolic pathways. This finding could be explored in future studies.